Understanding perceptual and adaptation to climate change by the saffron farmers Of the Kashmar plain - morteza esmailnejad (Zirā̒at va Fanāvarī-i Za̒farān, 2018)
Climate change has serious impacts on communities and livelihoods in dry areas. The agricultural sector accepts the greatest impact from climate change due to its extensive interactions with the environment. Environmental degradation and reduced yield of saffron and weakening of the household economy are among the consequences of climate change in the Kashmar plain. This study was carried out in order to evaluate the perception of saffron in the Kashmar plain from climate change and its capacity to adapt to this phenomenon. The present study was conducted to examine the perceptions and adaptation of saffron to climate change in order to expand the strategies for confronting the climate change challenges in the Kashmar plain. The method of this study is descriptive-analytic. The population of the study was calculated using Cochran's sampling method and a sample size of 390 households was chosen. Statistical models such as logistic regression were used to examine saffron perception and compatibility strategies. The analysis of saffron perceptions of climate change shows that the increase in temperature and the decrease in rainfall during the last decade in the Kashmar plain has been ongoing. The results of the logistic statistical model indicated that product diversity, change in crops, finding a job outside the farm, changing the amount of land, changing the planting date of saffron were adaptation methods used in the region. Given that many saffron growers have come to understand climate change and adjust their farming activities based on these changes, the government should facilitate the adaptation of saffron to climate change.